Strategi Pembelajaran Bagi Anak Berkebutuhan Autis Khusus Tantrum Di Sekolah Alam Mahira Kota Bengkulu - Nimas Ayu Ambar Wati; Asifah Nur Ihsani; Nopia Sapitri; Wennyta Pratama Putri; Fidhia Andani (JPT : Jurnal Pendidikan Tematik, 2023)
Children with Special Needs include children with disabilities, namely those who experience deviations or significant differences from the general (average) state of people, so they require special educational services so they can develop their potential optimally. These deviations can occur in physical, mental, social, and/or emotional aspects. Tantrums are a common behavioral problem experienced by preschool children who express their anger by sleeping on the floor, struggling, screaming and usually holding their breath. Tantrums are natural, especially in children who cannot yet use words to express their frustration (Fetsch & Jacobson, 1988). Temper tantrums are explosive and uncontrolled emotional outbursts. Tantrums occur in active children with abundant energy. This study was conducted using a qualitative research type with a descriptive qualitative research type that aims to describe the role of special education teachers in implementing special needs programs in schools. in implementing strategies, namely using ABA therapy strategies for children who experience temper tantrums.